Does Respiratory Variation in Inferior Vena Cava Diameter Predict Fluid Responsiveness in Mechanically Ventilated Patients? A Systematic Review and Meta-analysis. (November 2018) - Si, Xiang; Xu, Hailin; Liu, Zimeng; Wu, Jianfeng; Cao, Daiyin; Chen, Juan; Chen, Minying; Liu, Yongjun; Guan, Xiangdong
Abstract : BACKGROUND: We performed a systematic review and meta-analysis of studies investigating the diagnostic accuracy of respiratory variation in inferior vena cava diameter (ΔIVC) for predicting fluid responsiveness in patients receiving mechanical ventilation. METHODS: MEDLINE, EMBASE, the Cochrane Library, and Web of Science were screened from inception to February 2017. The meta-analysis assessed the pooled sensitivity, specificity, diagnostic odds ratio, and area under the receiver operating characteristic curve. In addition, heterogeneity and subgroup analyses were performed. RESULTS: A total of 12 studies involving 753 patients were included. Significant heterogeneity existed among the studies, and meta-regression indicated that ventilator settings were the main sources of heterogeneity. Subgroup analysis indicated that ΔIVC exhibited better diagnostic performance in the group of patients ventilated with tidal volume (TV) ≥8 mL/kg and positive end-expiratory pressure (PEEP) ⩽5 cm H2 O than in the group ventilated with TV <8 mL/kg or PEEP >5 cm H2 O, as demonstrated by higher sensitivity (0.80 vs 0.66; P = .02), specificity (0.94 vs 0.68; P < .001), diagnostic odds ratio (68 vs 4; P < .001), and area under the receiver operating characteristic curve (0.88 vs 0.70; P < .001). The best ΔIVC threshold for predicting fluid responsiveness was 16% ± 2% in the group of TV ≥8 mL/kg and PEEP ⩽5 cm H2 O, whereas in the group of TV <8 mL/kg or PEEP >5 cm H2 O, this threshold was 14% ± 5%. CONCLUSIONS: ΔIVC shows limited ability for predicting fluid responsiveness in distinct ventilator settings. In patients with TV ≥8 mL/kg and PEEP ⩽5 cm H2 O, ΔIVC was an accurate predictor of fluid responsiveness, while in patients with TV <8 mL/kg or PEEP >5 cm H2 O, ΔIVC was a poor predictor. Thus, intensivists must be cautious when using ΔIVC.